ASEP SUNANDAR SUNARYA: MENJADI DALANG WAYANG GOLEK YANG POPULER - Masyuning S.Sn., M.Sn. (Paraguna, 2017)
Not many people knew As~p Sunandar's journey whom became famous puppeteer in West Java. The topic about As~p Sunandar led me to research and write this paper. I began formulating the topic as sinden at As~p Sunandar's theater troupe. I know that I was doing ethnomusicology or fieldwork: by getting to know As~p Sunandar who make the new style of wayanggol~k performances, studying and performing the music itself, and talking to whoever had the patience to listen to me. The conclusion ofpaperwasAs~p Sunandarfocused on the innovative nature of the wayang gol~k performance.